Sex-Related Differences in Catheter Ablation for Patients With Atrial Fibrillation and Heart Failure - Chibber, Tamanna; Baranchuk, Adrian (Frontiers in Cardiovascular Medicine, 2020)
The co-existence of atrial fibrillation and heart failure significantly increases the risk of all-cause mortality and heart failure hospitalizations. Sex-related differences in all patients undergoing atrial fibrillation catheter ablation include fewer women referred for catheter ablation (15-25%), older age of women at ablation, and higher risk of post-ablation recurrence of atrial fibrillation. We searched the existing literature for sex-related differences in patients undergoing atrial fibrillation catheter ablation with a focus on heart failure. Randomized controlled trials assessing atrial fibrillation catheter ablation in patients with heart failure have demonstrated a significant reduction in all-cause mortality and heart failure hospitalizations. Within the eight existing randomized controlled trials on heart failure with reduced ejection fraction, women composed a small proportion of the study population. Only two studies (CASTLE-AF and AATAC-HF) specifically assessed the effect of gender on outcome, showing no difference in post-ablation outcomes. Registry data based studies assessing sex-related differences in atrial fibrillation catheter ablation in heart failure reveal that women are half as likely as men to undergo ablation. Conflicting data exists on the interaction of gender and heart failure as they may affect peri-ablation and post-ablation long term outcomes such as atrial fibrillation recurrence or heart failure hospitalizations. In conclusion, existing studies provide insight into the gender based differences in patients undergoing catheter ablation for atrial fibrillation as it pertains to heart failure. Further prospective studies with higher proportions of female participants are required to accurately determine gender based differences in this population.